Robotic-Assistance in Total Hip Arthroplasty Is Associated With Decreased Dislocation Rates - Gabrielle N. Swartz, BS; Sandeep S. Bains, MD, DC, MBA; Jeremy A. Dubin, BA; Reza Katanbaf, MD, MBA; Hunter Hayes, DO; James Nace, DO, MPT; Michael A. Mont, MD; Ronald E. Delanois, MD (Arthroplasty Today)
Background: As the use of robotics in total hip arthroplasty (THA) continues to gain popularity, differences in clinical outcomes when compared to manual techniques have remained unclear. This study aimed to compare postoperative complications between patients undergoing robotic-assisted techniques and manual THA for primary osteoarthritis at 90 days, 1 year, and 2 years. Methods: Using an all-payer national database, we identified 405,048 patients who underwent either robotic-assisted or manual THA for primary osteoarthritis. A propensity match was performed for age, sex, a comorbidity index, chronic kidney disease, obesity, and diabetes, resulting in 7652 patients in each cohort. We assessed postoperative outcomes, including surgical site infections, pulmonary emboli, venous thromboemboli, wound complications, dislocations, aseptic revisions, periprosthetic joint infections, and periprosthetic fractures. We completed bivariate analyses via chi-square tests to assess categorical variables. We utilized student’s t-tests to compare continuous variables, including ages and comorbidities. Odds ratios (ORs) were calculated for complications using 95% confidence intervals (CIs). Results: The robotic-assisted cohort had lower rates of dislocation at 90 days (0.93 vs 1.41%, OR 0.65, 95% CI 0.48-0.88, P = .007), 1 year (1.32 vs 1.92%, OR 0.68, 95% CI 0.53-0.88, P = .004), and 2 years (1.66 vs 2.1%, OR 0.79, 95% CI 0.62-0.99, P = .049). Total surgical complications were significantly lower in the robotic-assisted cohort at 1 year (5.29 vs 6.16%, OR 0.85, 95% CI 0.74-0.98, P = .0205), but were similar at 90 days and 2 years. At 90 days, the rates of medical complications, including surgical site infections, pulmonary emboli, venous thromboemboli, and wound complications, were similar (all P > .05). The rates of periprosthetic joint infections, aseptic revision, periprosthetic fractures, and aseptic loosening were similar at all time points (all P > .05). Conclusions: Patients who underwent robotic-assisted THA had lower rates of dislocation at 90 days, 1 year, and 2 years. This finding supports the use of robotic assistance in THA, though further research is needed to confirm and strengthen these findings.